2020
DOI: 10.1021/acs.cgd.9b01273
|View full text |Cite
|
Sign up to set email alerts
|

Compositionally Graded AlGaN Nanostructures: Strain Distribution and X-ray Diffraction Reciprocal Space Mapping

Abstract: The strain distribution in compositionally graded AlGaN planar structures, pillars, and nanowires (NWs) has been studied by three-dimensional (3D) strain calculations based on a numerical finite element method (FEM) and X-ray diffraction reciprocal space mapping. First, new fitting analyses of the reciprocal space maps (RSMs) are demonstrated to evaluate the depth profiles of strain and Al concentration, the film thickness, and the density of threading dislocation in compositionally graded AlGaN planar heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, the BVs of Str_A were significantly enhanced, as shown in figure 19(b). Furthermore, with increased buffer layer thickness, the BV can be further enhanced to 350 V. Additionally, it has been confirmed that graded AlGaN buffer layers can simultaneously improve the crystal quality by modulating the internal strain [118][119][120][121]. Therefore, this type of graded AlGaN back-barrier layer has been widely implemented in AlGaN electronic devices on Si [122][123][124], SiC [125], and sapphire substrates [126][127][128], contributing to the improved crystal quality of AlGaN epilayers and enhanced device performance.…”
Section: Graded Algan Back-barrier Layers For Sufficient Electronmentioning
confidence: 92%
“…Therefore, the BVs of Str_A were significantly enhanced, as shown in figure 19(b). Furthermore, with increased buffer layer thickness, the BV can be further enhanced to 350 V. Additionally, it has been confirmed that graded AlGaN buffer layers can simultaneously improve the crystal quality by modulating the internal strain [118][119][120][121]. Therefore, this type of graded AlGaN back-barrier layer has been widely implemented in AlGaN electronic devices on Si [122][123][124], SiC [125], and sapphire substrates [126][127][128], contributing to the improved crystal quality of AlGaN epilayers and enhanced device performance.…”
Section: Graded Algan Back-barrier Layers For Sufficient Electronmentioning
confidence: 92%
“…The dislocations in a crystal and other structural parameters such as the thickness, the alloy mole fraction, the lattice parameters can be calculated by X-ray diffraction (XRD) results, which is nondestructive method. 5,[15][16][17][18] To investigate the dislocation densities that include edge and screw types in terms of the structural quality is important, because the dislocations are one of the main effects that deteriorate the device performance of the HEMTs. [19][20][21] One of the main reasons for the dislocations is the strain relaxation that occurred at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…During the growth process of a crystal, unwanted defects, dislocations, and strain may have occurred. The dislocations in a crystal and other structural parameters such as the thickness, the alloy mole fraction, the lattice parameters can be calculated by X‐ray diffraction (XRD) results, which is nondestructive method 5,15–18 . To investigate the dislocation densities that include edge and screw types in terms of the structural quality is important, because the dislocations are one of the main effects that deteriorate the device performance of the HEMTs 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, proper engineering of both spontaneous and piezo-polarization fields permits the intentional and favorable tuning of the electronic properties of IIInitrides. For example, the activation of impurity dopants by the polarization charge in compositionally graded AlGaN semiconductors found very receptive applications in the fabrication of efficient DUV-LEDs and p-n junctions [23][24][25][26][27]. This polarization doping depends intimately on biaxial strain (piezo-polarization) and alloy composition (spontaneous polarization).…”
Section: Introductionmentioning
confidence: 99%